Study on the Electro-Osmosis-Combined-Preloading Method in Strengthening Reclaimed Sludge from the Macroscopic and Microscopic Views - Yanli Tao; Jianfeng Zhu; Jian Zhou; Zeyi Yu; Jia Lu (Journal of Marine Science and Engineering, 2022)
The electro-osmosis-combined-preloading method is considered very promising in soft soil improvement, while the uncertainty in the function mechanism has hindered its practical application. To explore the mechanism of the combined method, experiments concerning the single electro-osmosis method and the combined method were carried out using reclaimed sludge. Macroscopic and microscopic properties of the soil were explored and compared. Drainage, soil settlement, soil water content and soil pore structure were detected during the experiments. The total drainage and average settlement of the combined method were, respectively, 20.8% and 34.5% greater than that of the single electro-osmosis method. The average void ratio of soils treated by the combined method was 13.8% lower than that by the electro-osmosis method. Moreover, reduction rates of the soil water content are found higher than that of the apparent void ratio for each method. It can be concluded that the combined method had better performances, both from the macroscopic and microscopic views. Furthermore, a theoretical analysis demonstrated that soil was desaturated and the soil shrinkage volume was lower than the drained water volume during electro-osmosis. This is derived from the essence of electro-osmosis, which determines that considerable pores formerly occupied by drained water cannot be effectively compressed. The combined method can fully use the advantages of the single methods by active drainage through electro-osmosis and further compression of the soil skeleton through preloading. Therefore, the electro-osmosis-combined-preloading method was strongly recommended for reclaimed sludge strengthening.